Parent Involvement in Pre-school Science Activities: What Do Parents Think About It? - Cigdem Sahin Cakir; Gonca Uludağ (Universitas Pendidikan Indonesia, 2022)
This study aimed to investigate parents' views about science and parent involvement in pre-school science activities. According to Cresswell's designs' sequential explanatory mixed-method design, the study was conducted. The participants were composed of parents of 39 children (60-72 months) who studied in two different classrooms, there were 20 children in one of the classrooms, and there were 19 children in the other classroom at a public pre-school in Ankara/Turkey in 2015-2016 school year. The Parents' Views about Science and Preschool Science Activities Scale and semi-structured interviews were used to collect data. In addition, semi-structured interviews were conducted with three volunteer parents, each from the parents who got high, medium, and low average scores from the scale. Thus, parents' views about science and parent involvement in pre-school science activities were examined in detail. According to the results of this study, it was determined that the parents who participated in this study had positive views on science and science education in pre-school, realized the importance of science activities in pre-school, were eager to participate in pre-school science activities. Therefore, this study suggests that teachers and parents should be informed that parents' involvement is essential for doing science activities in pre-school.